Attitude and perception of farmers to the implementation of conservation farming in the mountainous area of South Sulawesi. (May 2018) - Busthanul, N; Lumoindong, Y; Syafiuddin, M; Heliawaty,; Lanuhu, N; Ibrahim, T; Ambrosius, R R
Abstract: Farmers' attitudes and perceptions may be the cause of ineffective implementation of conservation farming for agriculture sustainability due to vary of implementing of conservation techniques. The purpose of this research is to know the attitude and perception of farmer toward the application of conservation technique and to know correlation between farmer attitude and perception toward the application of conservation technique. The research was carried out in Kanreapia Village, Tombolo Pao District, Gowa Regency, South Sulawesi Province, Indonesia. Sampling was done by randomly with 30 farmers; using non-parametric statistics with quantitative and qualitative descriptive data analysis approach, using Likert scale. The result showed that farmer attitude and perception toward conservation technique implementation which having the highest category (appropriate) is seasonal crop rotation, while the lowest with less appropriate category is the processing of land according to the contour and the cultivation of the plants accordingly. There is a very strong relationship between farmer attitude and perception. The implications of the findings are that improvements the implementation of conservation farming techniques should be made through improved perceptions.